PENGARUH PENAMBAHAN FLY ASH TERHADAP KUAT TEKAN, BERAT JENIS, DAN DAYA HAMBAT PANAS BATA BETON RINGAN FOAM SEBAGAI SUPLEMEN BAHAN AJAR MATA KULIAH TEKNOLOGI BETON PADA MAHASISWA SEMESTER III PTB JPTK UNS - Ngarifin, Ngarifin; Habsya, Chundakus; Rahmawati, Anis (Universitas Sebelas Maret, 2015)
The purposes of this research were, (1) determine the effect of fly ash added withvariations of 0%, 10%, 20%, 30% and foam added with variation 30% and 40% oncompressive strength, density, and thermal gacorqq resitance of lightweight foam concrete bricks, (2)determine the percentage of fly ash and foam that gacorqq produces thermal resistance that satisfiedrequired compressive strength on lightweight foam concrete bricks SNI 03-2847-2002. (3)determine the percentage of fly ash and foam added that produces minimal densitylightweight foam concrete bricks, and (4) produce supplement teaching materials obtained inthe course of concrete technology on the effect of the fly ash addition to the compressivestrength, density, and thermal resistance of lightweight foam concrete bricks.This research used experimental method and data analysis techniques used regressionanalysis. Variables in the study were (1) dependent variables: compressive strength, density,and thermal resistance of lightweight foam concrete bricks, (2) independent variables: the flyash addition with variations 0%, 10%, 20%, and 30% to the needs of fine aggregate andvariations addition of foam 30% and 40% of the concrete volume with the water and foamagent ratio = 1:40.Based on the results of the study concluded that, (1) variation of the addition of flyash and foam was strongly influencing the compressive strength, density, and thermalresistance of lightweight foam concrete bricks, (2) thermal resistance with concludedcompressive strength on lightweight foam concrete bricks SNI 03-2847-2002 produced from30% of the concrete volume foam added with the percentage fly ash added of 10%, 20%, and30% of fine aggregate respectively were 27.6 kg /cm2; 29.3 kg/cm2; and 35.0 kg/cm2, (3) theminimal density of lightweight foam concrete bricks produced on the percentage of fly ashaddition of 0% (without the fly ash addition) with 40% foam addition of the concrete volumethat was 855.565 kg/m3, (4) produced gacorqq tecahing materials in the form of supplements teachingmaterials about the effect of the fly ash addition to the compressive strength, density, andthermal resistance of lightweight foam concrete bricks.Keywords: fly ash, foam, lightweight foam concrete brick, compressive strength, density,thermal resistance.